ATURAN BERPRILAKU DI TEMPAT SUCI MENURUT LONTAR KRAMAPURA - I Nyoman Suka Ardiyasa; Ida Bagus Gede Paramita (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2017)
behaving. Not infrequently Hindus are trapped in a behavior that is not in accordance with sesana as Hindu, so it affects the behavior that deviates. The phenomenon of Hindus dressed in fashion to the temple, the number of gambling operations in the plate of Pura is a deviant behavior that is not in accordance with sesana as Hindus. So it needs to be explored guidelines to behave for Hindus. One of the guidelines for behaving in the shrine is the Lontar Kramapura Manuscript. This manuscript text is a type of papyrus Sesana that contains the teachings of behavior to maintain the sanctity of the temple. This Lontar Manuscript outlines the teachings and prohibitions that are not allowed if you want to enter the temple. The teachings contained in this Lontar Kramapura (1) The doctrine of preserving the sanctity of the Pura where this doctrine contains the duties for the pengempon and pemaksan Pura to keep the holiness is maintained. (2) The Doctrine of Sesana Pemangkuan, in this doctrine contains the obligations of stakeholders as Pangempon Pura in maintaining the sanctity and sacredness of the temple through the improvement of jnana with the obligation to learn sesana become Pemangku. This manuscript of Lontar Kramapura also contains restrictions on holy places such as (1) Various kinds of offerings that should not be placed in the temple, (2) Prohibition for people entering temples like for men who are menstruating, cuntaka and others. (3) Prohibition for people who behave badly like confessing kerauhan, stealing in the temple, saying that is not good at the temple, people who fight in the temple, and behave that do not know the courtesy.